2019
DOI: 10.1590/1980-5373-mr-2018-0099
|View full text |Cite
|
Sign up to set email alerts
|

Failure Theories on Carbon/Kevlar Hybrid Fabric Based Composite Laminate: Notch and Anisotropy Effects

Abstract: Composite materials have been increasingly used in both researches and industries, given their wide range of innovative applications and configurations. High-performance hybrid fabric-reinforced plastics stand out in this sector. In the present research, an epoxy-based vinyl ester resin laminate reinforced with bidirectional hybrid fabric consisting of carbon and Kevlar fibers is developed. In order to determine its mechanical properties and damage mechanism considering the anisotropy and the presence of geome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…show that Elastic modulus and tensile stress increase when carbon fibers ratio increase and 3C-Ep30% composite material have the higher elastic modulus and tensile strength. That was attributed to the higher tensile properties of carbon fibers compared to Kevlar fibers [16]. In addition, the used Carbon fabric is surface treated in the manufacturing company with silane coupling agent, which improves the chemical bonding between carbon fibers and epoxy.…”
Section: Fabrics/epoxy Non-hybrid Compositesmentioning
confidence: 99%
“…show that Elastic modulus and tensile stress increase when carbon fibers ratio increase and 3C-Ep30% composite material have the higher elastic modulus and tensile strength. That was attributed to the higher tensile properties of carbon fibers compared to Kevlar fibers [16]. In addition, the used Carbon fabric is surface treated in the manufacturing company with silane coupling agent, which improves the chemical bonding between carbon fibers and epoxy.…”
Section: Fabrics/epoxy Non-hybrid Compositesmentioning
confidence: 99%
“…The scenario with the open hole is the topic of this research. Research into the open hole of hybrid composite laminates has been one of the recent focuses [ 19 , 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The use of multiple types of fibers in a single laminate allows the designer to fine-tune the properties of the laminate to the design requirements [ 22 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. Hybridization is expected to gain some enhancement from some properties.…”
Section: Introductionmentioning
confidence: 99%
“…Although there has been a lot of research analysing the mechanical performance of carbon/epoxy composites and Kevlar/epoxy composites in the literature [ 5 , 33 , 34 , 35 ], a lack of information exists regarding some mechanical properties of carbon/aramid/epoxy hybrid composite. For example, there are no publications investigating the Poisson’s ratio, because the authors reported only the tensile strength and modulus of elasticity [ 36 ]. The most recent research aimed to analyse the impact and post-impact properties of the composite materials reinforced with carbon-aramid fabrics [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%